Correlation between Exclusive Breastfeeding, Complementary Feeding, Infectious Disease with Wasting among Toddlers: a Cross-Sectional Study - Ani Intiyati; Rany Dwi Yuliana Putri; Imam Sarwo Edi; Taufiqurrahman Taufiqurrahman; Inne Soesanti; Nuning Marina Pengge; Dian Shofiya (Amerta Nutrition)
Background: Wasting, an acute nutritional deficiency, is assessed using weight-for-height with a z-score of <-2SD from growth standards. The prevalence of wasting in Puskesmas Kendit is 14.31%, with Kukusan Village at 29%.